Organocatalytic route to the synthesis of lactone moiety of compactin and mevinolin - Kumar, Pradeep; Pandey, Menaka; Gupta, Priti; Dhavale, Dilip D. (Tetrahedron Letters, 2010)
An efficient synthesis of lactone moiety of compactin has been achieved. The stereogenic centers were generated by means of iterative proline-catalyzed sequential alpha-aminoxylation and Horner-Wadsworth-Emmons (HWE) olefination of aldehydes. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Aminoxylation; Compactin; Lactone; organocatalysis; Proline

Organocatalytic stereoselective synthesis of passifloricin A - Kumar, Pradeep; Pandey, Menaka; Gupta, Priti; Dhavale, Dilip D. (Organic & Biomolecular Chemistry, 2012)
The enantioselective synthesis of passifloricin A has been achieved in high diastereomeric excess. The 1,3-polyol moiety was constructed by iterative proline-catalyzed sequential alpha-aminoxylation and Horner-Wadsworth-Emmons (HWE) olefination of aldehydes while the synthesis of lactone moiety was achieved by ring-closing metathesis (RCM).